Media Spectacle as Political Epistemology: The Real-Time Construction of Presidential Impeachment - Yergensen, Brent (New Explorations)

(untitled) (New Explorations Association, 2024)
Murray Edelman argued that political news on television creates spectacles, which render viewers influenced by the emotional production process of publicized events coverage. Yet, the digital age renders spectacle functioning more intimately with audience than during Edelman’s original treatment in 1989. Drawing upon psychoanalytic and epistemological theory, I contextualize Edelman’s theory regarding the real-time opportunity of spectacle coverage, or not. Considering that media spectacle efficacy has to do with experiencing the spectacle as live events, I make the case that real-time coverage plays a role in the media construction of audience perception. The case analysis considers the history of presidential impeachments, with differentiation drawn between fresh news driven impeachments versus post-events attempts at charging national leaders. This is explored more particularly in the impeachment efforts against Presidents Bill Clinton and George W. Bush. The media empowerment of spectacle is explored further in relation to digital and social media, the opining polarization of participatory politics, and the growth of impeachments, particularly in the age of Donald Trump social media organizing and news development, and in the shadow of his being the first president to be impeached twice while in office.